Effectiveness of Islamic Religion Education Learning With Principal of Different Religion (Case Study in Elementary School Burengan 2 Kediri) - Aziz, Mohammad Abdulloh (Didaktika Religia, 2018)
This study discusses the effectiveness of learning Islamic Education in a broad sense. The effectiveness is also supported by the role of school principal who is very active even though the principal is of different religion. Various learning activities in schools are facilitated and evaluated very well. Learning that takes place in the classroom is more dominant using the demonstration method because it is considered easier. In addition, among the learning activities that are quite visible are BTQ Extracurricular activities with Tilawati Method where this activity takes tutors from other institutions that require substantial funds. The other activities, namely PHBI, were actively commemorated, especially in the Commemoration of Eid al-Adha, which was never absent to slaughter Qurban animals. Various perspectives that say religion will influence a policy in this school do not happen the principal is very wise in deciding a decision. Religious teachers here always establish good communication with the principal so that every learning that occurs will run optimally. Learning activities in this school prioritize psychomotor or behavioral aspects but does not mean to put aside the affective side. All the learning processes aim to form students who are devoted, accomplished, and have character